A3TV: uma ferramenta para produção e distribuição de canais de televisão no contexto da TV 2.0 - Oliveira, Felipe Soares de (2010)
In the last years, the Internet is improving communication and broadcasting services. Television, in the way we know it, is also evolving in order to add new services and formats, specially with the advent of Digital TV. In this scenary of digital convergence, collaboration and customization facilities are becoming possible and accessible through Internet and television. The approaching of Web 2.0 enlarges the vision of internet as merely a computer network to a further social vision, made by individuals that are members of communities communicating to each other in a collaborative process. In this work we study the evolution of television after the appearing of technologies emerged from Internet, as well as the convergence among these systems. As a result it was proposed a model which conceives the characteristics that come from this convergence, which was called TV 2.0, and was developed a technological solution to validate it. This solution is called A3TV (from English Anytime, Anywhere and by Anyone TV), which aims to reinforce the experience of TV inside accessed through Internet, making available tools for creation, collaboration and distribution of TV programs. In this tool it is possible to acquire and to manage contents and to create television channels accessible through the Internet.